Figured funerary stelai from Roman-period Anatolia, 100 BC-AD 400: regional considerations of cultural, social, and economic expressions in funerary contexts - Taylor, S (2020)
This thesis presents a multi-faceted, case-study based examination of regionalism and use of figured funerary stelai from fifteen sites in Roman-period Asia Minor and Galatia, focusing on local patterns of iconography and epigraphy as well as broader regional comparison of these trends. These non-door stelai, a sample of 302 monuments, are flat-face stones decorated with relief figures from a narrow selection of iconographic-types. This study offers a synthesis of all aspects of figured-stele use in the case-study sites, encompassing constituent elements of the monuments and consideration of stele-use between city and countryside, taking into account local geo-political histories, and approaching stelai as simultaneously private and public monuments of self-display. Section I focuses on stelai in the sepulchral landscape of Roman-period Anatolia, the technical details of the stelai themselves, and situating stelai in the economics of commemoration. There follows in Section II a detailed assessment of the iconography and epigraphy of the case-study figured stelai. Questions of represented socio-economic levels, stele-use vis-à-vis settlement patterns, and regional customs of commemoration are the subject of Section III, exploring relationships between patrons, deceased, and stele components. Iconography and epigraphy on these monuments highlight the ‘standardization’ of motifs in the Roman period and local shifts in image emphases and patron priorities, including the development of more individualized iconography with the expanded socio-economic spectrum employing this monument to include not only some ‘elite’ but also gladiators and farmers among other occupations. Similar expansion appears in the geographic distribution of figured stelai, incorporating regions with limited pre-Roman traditions for the monument. The simultaneous broadening of both the socio-economic levels of patrons and the geographic regions of use represent distinguishing characteristics of Roman-period figured-stele patterns.